Synthesis of (1R,2R)-1,2-bis-(5-(4-hydroxynaphthalen-1-ylazo)[1,3,4]thiadiazol-2-yl)-ethane-1,2-diol - Koparir, M; Cansiz, A; Cetin, A; Kazaz, C (Springer, 2005)
In this study, (1P,2R)-1,2-bis-(5-amino-1,3,4-thiadiazol-2-yl)ethane-1,2-diol (2), was synthesized by using (2R,3R)-(+)-Tartaric acid (1) as starting compound. Then the diazo component 3 was obtained from 2 and 1-naphthol. In addition, the structures of the synthesized compounds 2 and 3 were confirmed by elemental analyses, IR, H-1-NMR, and C-13-NMR spectra.
Keywords: tartaric acid; thiadiazole; dye compounds